Digital Learning Transformation in Higher Education: International Cases of University Efforts to Evaluate and Improve Blended Teaching Readiness - Charles R. Graham; Ganbat Danaa; Tserenchimed Purevsuren; Adriana Martínez; Cinthia Bittencourt Spricigo; Barbara Maria Camilotti; Tserenkhand Batsukh (MDPI AG, 2023)
The global pandemic of 2019 brought heightened awareness to institutions of higher education of the need to engage in a digital transformation that extends beyond university business operations to the pedagogy of the classroom. This paper is a case study that explores three international cases of universities in Colombia, Brazil, and Mongolia that are at different stages along the path of a digital pedagogical transformation. This article tells each story, including (1) what is driving the local need to engage in digital transformation, (2) what the major challenges and barriers are to achieving a transformation, and (3) what efforts are being made to help each university to move along the path towards adoption and change. It concludes with discussing three major themes that emerged from the case studies: (1) the role of local policy in shaping digital transformation, (2) the importance of developing human capacity with technology, and (3) the potential for digital transformation to bring hope.